The 3 C’s of Consideration for COVID-19 Workplace Fever Detection Device Selection: Context, Calibration & Cost - Goggins, Katie A; Tetzlaff, Emily J; Gauthier, Sara N; Young, Wesley W; Godwin, Alison A (International Journal of Occupational Safety and Health, 2022)
COVID-19 screening protocols have become normal practice for employees entering workplaces around the world. However, workplace screening programs that include temperature detection via infrared thermometers or thermal detection cameras often violate many technical specifications for the correct use of these devices. Therefore, this article aims to provide practical guidance for non-thermal imaging specialists responsible for selecting thermal detection devices for workplace screening protocols. Focusing on three critical points of consideration, including the context of use, calibration of equipment, and cost of purchase and maintenance, readers are presented with a framework to guide their decision-making. This framework not only prioritizes the health and wellbeing of employees by ensuring the context of use is appropriate but balances the cost of calibration, purchasing and additional supporting supplies. Further, the presented framework extends beyond the COVID-19 pandemic and can be easily adapted to implement any new workplace technology.